2004
DOI: 10.1111/j.1479-828x.2004.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and birth outcome: New Zealand trends 1980–2001. Part 1. Introduction, Methods, Results and Overview

Abstract: The marked differences in both trend data and risk factor profiles for women in New Zealand's largest ethnic groups would suggest that unless ethnicity is specifically taken into account in future policy and planning initiatives, the disparities seen in this analysis might well persist into future generations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 9 publications
(11 reference statements)
3
35
1
Order By: Relevance
“…A previous New Zealand study, with limited demographic and obstetric data have shown an increased risk of stillbirth among both Pacific Island and Indian mothers. 8 The present study which was able to control for a greater range of maternal and obstetric factors also found an increased risk in these ethnic groups. The mechanisms behind these increased risks are unclear.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A previous New Zealand study, with limited demographic and obstetric data have shown an increased risk of stillbirth among both Pacific Island and Indian mothers. 8 The present study which was able to control for a greater range of maternal and obstetric factors also found an increased risk in these ethnic groups. The mechanisms behind these increased risks are unclear.…”
Section: Discussionmentioning
confidence: 62%
“…A recent series of publications [8][9][10][11] reported that women of Pacific Island and Indian ethnicity had higher rates of stillbirth compared with European women. This study used national datasets that contained limited information about maternal demographics, and no data about previous pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…[17][18][19][20] When the social gradient in health is analyzed in relation to wealth, the relationship is continuous, implying that there is no threshold above which health inequalities disappear. 21 Additionally, individuals with comparable incomes but who differ in occupational rank generally exhibit differences in health that mirror their respective social positions.…”
Section: Introductionmentioning
confidence: 99%
“…However, less research has evaluated trends in ethnic-based inequalities over time. Although there is evidence that BlackWhite disparities in PTB have been stable in the US since the 1990s [20], disparities between ethnic groups in New Zealand may be increasing [38]. For SGA birth, BlackWhite disparities in the US were stable for term SGA birth * Adjusted for country of birth, language spoken at home, age, education, marital status, previous deliveries, infant sex (except for small-for-gestational-age birth), and period but increased for preterm SGA birth during the latter half of the last century [39,40].…”
Section: Discussionmentioning
confidence: 95%